Self-Affirmation through the Choice of Highly Aesthetic Products - Townsend, Claudia; Sood, Sanjay (Journal of Consumer Research, 2012)
Abstract Just as good looks bestow an unconscious “beauty premium” on people, high aesthetics bestows an unrecognized benefit on consumer goods. Specifically, choosing a product with good design affirms the consumer’s sense of self. Choice of a highly aesthetic product was compared with choice of products superior on other attributes including function, brand, and hedonics to show that only aesthetics influences a consumer’s personal values. In study 1 a prior self-affirming task leads to a decrease in choice share of a highly aesthetic option. Studies 2 and 3 mimic prior research on self-affirmation with, however, choice of a highly aesthetic product replacing a traditional self-affirmation manipulation. Choosing a product with good design resulted in increased openness to counter-attitudinal arguments and reduced propensity to escalate commitment toward a failing course of action. There are numerous implications of this form of self-affirmation, from public policy to retail therapy.